Implementation of Total Quality Management (TQM) in Improving School Quality - Ridwan, Wawan; Adang Hambali; Hasan Basri; Dadan Nurul Haq; Meenu Sharma (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The growing demand for integrated Islamic schools to deliver high-quality education that emphasizes both academic excellence and character development has encouraged the adoption of Total Quality Management (TQM) as a modern and relevant management approach. TQM is considered appropriate because it highlights continuous improvement, active involvement of all school members, and a strong focus on customer satisfaction within the educational context. This study aims to analyze the implementation of TQM in improving school quality at three integrated Islamic junior high schools: SMP IT Al-Khoiriyyah, SMP IT Nurul Islam, and SMP IT Baitul Anshor. The research employed a qualitative method using a multi-case study design. Data were collected through in-depth interviews, direct observations, and document analysis involving principals, vice principals, teachers, educational staff, students, and parents. Data analysis followed the stages of reduction, presentation, and inductive conclusion drawing. The findings indicate that TQM implementation in all three schools followed four main stages: planning, organizing, implementation, and monitoring and evaluation. During planning, TQM principles were embedded in School Work Plans, the PDCA cycle was applied, and stakeholders were actively involved. Organizing focused on quality-based structures, clear task distribution, and teamwork. Implementation included quality-oriented learning, teacher development, extracurricular activities, and integrated Islamic programs, while monitoring involved supervision, internal audits, evaluation meetings, and feedback systems. Supporting factors included visionary leadership, Islamic work culture, and parental support, while challenges involved limited facilities, uneven teacher competencies, and heavy workloads.